Ocean warming increases the nitrogen demand and the uptake of organic nitrogen of the globally distributed seagrass Zostera marina - Alexandre, Ana (2020)
The impact of global warming on the metabolic state of a species may be examined by either measuring physiological rates across a latitudinal gradient or by assessing short-term responses under experimentally controlled temperature regimes. The combination of the two approaches is seldom used but it provides valuable information on an organism's responses to temperature at broader temporal and spatial scales while allowing the isolation of temperature effects from other environmental variables. Here we used both approaches to assess the warming effects on the total acquisition of dissolved inorganic nitrogen (DIN; nitrate, ammonium) and organic N (DON; amino acids, peptides) by the globally widespread seagrass Zostera marina. DIN and DON uptake rates were measured in plants from three sites covering the species latitudinal distribution in Europe (Iceland, UK and Portugal). The responses of DIN and DON uptake rates of plants from the middle latitude (UK) to a latitudinal range of temperatures (8, 12 and 17 degrees C) were also measured. We further examined the microbial uptake of DON along the latitudinal distribution and whether temperature is the main driver of that uptake. Our results showed that warming greatly increased the total N uptake by Z. marina and also the relative contribution of DON to total N acquisition. The microbial uptake of DON increased towards warmer latitudes, and temperature was the main driver of these observations. Ocean warming will increase the nitrogen demand of Z. marina and this demand may be met by an increasing uptake of organic nitrogen forms. This indicates that Z. marina, and probably other seagrass species, can be winners under global change as nitrogen uptake capacity will not limit growth driven by increased photosynthetic assimilation of CO2.